Automatically Moving Robot Intended for the Elderly with Voice Control - Piyaneeranart, Manussawee; Ketcham, Mahasak (International Journal of Online and Biomedical Engineering (iJOE), 2021)
This research aims at an automatically moving robot intended for the elderly with voice control using voice recognition that gives a direction to the robot by a voice command. The development of this robot employed an algorithm that converts voice to text to control the robot mobility. The performance testing of the automatically moving robot intended for the elderly with Thai language voice commands revealed an accuracy of voice-to-text conversion for commanding the robot to move in designated directions of 100 percent, and the accuracy of voice-to-text conversion for commanding the robot to move in designated directions using English language was 80 percent, while that for both Thai and English commands was 70 percent. Errors in voice-to-text conversion occurred when commands were not clearly spoken or pronounced or when commands were issued from people located in a very noisy place.